2010
DOI: 10.1590/s1677-55382010000400010
|View full text |Cite
|
Sign up to set email alerts
|

Urinary proteomics evaluation in interstitial cystitis/painful bladder syndrome: a pilot study

Abstract: Purpose: Interstitial cystitis/painful bladder syndrome (IC/PBS) is characterized by chronic pain, pressure and discomfort felt in the pelvis or bladder. An in-depth shotgun proteomics study was carried out to profile the urinary proteome of women with IC/PBS to identify possible specific proteins and networks associated with IC/PBS. Materials and Methods: Urine samples from ten female IC/PBS patients and ten female asymptomatic, healthy control subjects were analyzed in quadruplicate by liquid chromatography-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 34 publications
(21 reference statements)
1
25
0
1
Order By: Relevance
“…Our in vitro studies indicated enhanced cell proliferation in IC/PBS urothelial cells compared to normal. These data agree with urinary proteomics studies that have identified upregulation of proteins involved in responses to wounding in IC/PBS patients [33]. In vivo , the secretion of APF, or other adaptive responses, may negate any beneficial effect of enhanced ERK 1/2.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our in vitro studies indicated enhanced cell proliferation in IC/PBS urothelial cells compared to normal. These data agree with urinary proteomics studies that have identified upregulation of proteins involved in responses to wounding in IC/PBS patients [33]. In vivo , the secretion of APF, or other adaptive responses, may negate any beneficial effect of enhanced ERK 1/2.…”
Section: Discussionsupporting
confidence: 90%
“…A recently published study [33] used urinary proteomics for normal and IC/PBS patients and identified several proteins and pathways that may contribute to IC/PBS pathology. Data from our laboratory and others suggests that there are biochemical changes that could enhance or impede cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Goo et al [45] analyzed the urinary samples from ten female healthy persons by LC coupled with a hybrid linear ion trap-orbitrap mass spectrometer and identified 1,003 urinary proteins. Li et al [46] used urines from three healthy male donors, and digested peptides were fractionated by two approaches, integrated multidimensional liquid chromatography and Yin-Yang multidimensional liquid chromatography methods.…”
Section: High-resolution Ms Analysismentioning
confidence: 99%
“…Commonly occurring conditions such as interstitial cystitis and painful bladder syndrome (IC/PBS) generate chronic pain, with pressure and discomfort in the pelvis or bladder. Goo et al 221 were interested in discerning not just the proteins whose expression were altered under these conditions but also the pathways and networks that may be coordinately regulated. In their pilot study, of the 78 proteins that were differentially expressed between IC/PBS and controls, α-1 β-glycoprotein and orosomucoid were both increased in more than 60% of the IC/PBS cohort.…”
Section: Interstitial Cystitis and Painful Bladder Syndromementioning
confidence: 99%